Corrosion-resistant crosslinked cable and preparation method thereof
By using magnesium, aluminum, silver, rare earth alloys in the cable and coated with graphite fibers and carbon fiber mesh, the problem of cable corrosion in acid rain, seawater and soil environments is solved, and the effects of high conductivity, strong mechanical properties and corrosion resistance are achieved.
Patent Information
- Application Number
- CN202510315309.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-17
- Publication Date
- 2025-06-17
AI Technical Summary
Existing cables are prone to corrosion in acid rain, seawater and soil environments, resulting in a decrease in conductivity and shortened service life, affecting the stability of the power system.
The alloy is made of magnesium, aluminum, silver and rare earth, and the surface is coated with graphite fiber composite material and carbon fiber web, and finally coated with a low-density polyethylene protective layer to form a corrosion-resistant crosslinking cable.
It achieves high conductivity, high mechanical properties and corrosion resistance, extends the service life of the cable and improves the stability of the power system.
Smart Images

Figure BDA0005315779000000091 
Figure BDA0005315779000000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cables, and specifically to a corrosion-resistant cross-linked cable and a preparation method thereof. Background Art
[0002] With the continuous expansion of the scales of industries such as China's power industry, data communication industry, urban rail transit industry, automotive industry, and shipbuilding industry, the demand for wire and cable will also increase rapidly. Among them, power cables are used to transmit and distribute electric energy. Power cables are commonly used in urban underground power grids, outgoing lines of power stations, internal power supply of industrial and mining enterprises, and underwater power transmission across rivers and seas. In power lines, the proportion of cables is gradually increasing. Power cables are cable products used to transmit and distribute high-power electric energy in the main lines of the power system, including power cables of various voltage levels from 1 - 500 kV and above and various insulations. In recent decades, energy consumption and climate change have become two major issues that countries around the world focus on. With industrial development, due to coal combustion, the contents of NO x , SO2, and CO2 in the atmosphere have increased, which has led to global acid rain environmental problems and the greenhouse effect. The greenhouse effect will cause the average temperature of the earth to rise continuously, thereby leading to a gradual rise in sea level. At the same time, with industrial development, various cables for various purposes are also laid underground. Acid rain, seawater, and soil environments are the main reasons for the failure of a large number of cables, causing huge economic losses to countries around the world. Data shows that the corrosion rate of metal materials exposed in acid rain areas, seawater, and soil environments is several to dozens of times faster than that in aqueous solutions, which greatly affects the function of cables and shortens the service life of cables. If one of these aspects of the cable structure does not meet the standard, it will affect the stability of the entire line. If problems occur, the subsequent work will be very complicated. Therefore, cables should have good long-term corrosion resistance and not cause a decrease in conductivity due to corrosion, which is an important condition for ensuring the normal operation of the power system. Summary of the Invention
[0003] The purpose of the present invention is to provide a corrosion-resistant cross-linked cable and a preparation method thereof to solve the problems existing in the prior art.
[0004] To solve the above technical problems, the present invention provides the following technical solution: A corrosion-resistant cross-linked cable, characterized in that the corrosion-resistant cross-linked cable is made of an alloy of magnesium, aluminum, silver, and rare earth, and graphite fibers are compositely coated on its surface, and then a net made of carbon fiber braiding is coated on the surface of the composite material; The preparation method of the corrosion-resistant cross-linked cable includes the following preparation steps:
[0005] (1) Heat the magnesium alloy and aluminum ingot to 750 - 900 °C to fully melt them. Add rare earth materials, then heat to 1200 - 1500 °C and stir at 40 - 80 rpm for 40 - 70 min. Subsequently, cool to obtain intermediate A;
[0006] (2) Heat the magnesium alloy and aluminum ingot to 750 - 900 °C to fully melt them. Add intermediate A and oxygen-free silver, then heat to 900 - 1100 °C and hold for 12 - 20 min. Press hexachloroethane into the bottom of the molten metal for stirring to degas and slag, then remove the surface dross, pour into a mold and cool for shaping. Then, perform homogenization annealing at a temperature of 360 - 450 °C for 10 - 15 h. Next, perform ultrasonic shot peening and oxidation treatment in sequence to obtain the alloy material;
[0007] (3) Cut the expanded graphite paper with a thickness of 0.5 mm into filaments, wrap it around the alloy material to obtain a composite conductive material. Then, weave and wrap carbon fiber around the composite material to form a carbon fiber net with a thickness of 0.5 - 2 mm. Finally, cover it with low-density polyethylene with a molecular weight of 153500 as a protective layer with a thickness of 2.5 mm to obtain a corrosion-resistant cross-linked cable.
[0008] Furthermore, the mass percentages of the chemical components of the magnesium alloy in step (1) are as follows: magnesium 94.94%, aluminum 3.5%, silicon 1.5%, zinc 0.04%, iron 0.01%, copper 0.01%.
[0009] Furthermore, the rare earth materials in step (1) are composed of cerium powder, lanthanum powder, and yttrium powder in a mass ratio of 1:1:1.
[0010] Furthermore, the mass ratio of the magnesium alloy, aluminum ingot, and rare earth materials in step (1) is 5:5:0.5 - 2.
[0011] Furthermore, the dosage of hexachloroethane in step (2) is 0.3 - 0.4% of the furnace charge.
[0012] Furthermore, the process parameters of the ultrasonic shot peening in step (2) are as follows: the shot peening pellets are 100CR6 rolling bearing steel balls with a diameter of 2 mm, the number of pellets is 300, the air pressure is 0.1 MPa, the moving speed of the nozzle is 1.5 m / min, the ultrasonic power is 1500 W, the frequency is 21 kHz, and the time is 40 - 100 s.
[0013] Furthermore, the conditions of the oxidation in step (2) are: the temperature is 500 - 600 °C and the time is 40 - 80 min.
[0014] Furthermore, the mass ratio of the magnesium alloy, aluminum ingot, intermediate A, and oxygen-free silver in step (2) is 5:5:0.5 - 1:0.5 - 2.
[0015] Furthermore, the length of the filament in step (3) is 25 to 50 cm and the width is 0.5 to 1 mm.
[0016] Furthermore, the weight of the carbon fiber mesh in step (3) is 150 to 250 g / m 2 , strength is 3000~4500MPa.
[0017] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0018] The cable of the present invention is made of an alloy of magnesium, aluminum, silver and rare earth, and graphite fiber is compositely coated on the surface thereof, and then a mesh woven from carbon fiber is coated on the surface of the composite material to achieve high electrical conductivity, high mechanical properties and corrosion resistance.
[0019] Firstly, magnesium and aluminum are used as the matrix, and silver is dispersed in the alloy matrix as the second phase to form a solid solution, and an aluminum-silver alloy or an aluminum-magnesium-silicon alloy strengthening phase is generated, thereby improving the corrosion resistance of the matrix and achieving conductivity. At the same time, rare earth elements are added to allow elements with the same precipitation phase structure to interact with each other, thereby increasing the solubility of the alloy elements in the magnesium and aluminum matrices, which is beneficial to the solid solution strengthening effect of the alloy elements, thereby achieving the effects of refining the grains, improving the electronegativity of each micro-region on the surface of the synergistic material, and stabilizing the protective film layer, thereby improving the corrosion protection performance of the alloy. Next, ultrasonic shot peening is performed. Under the action of high-energy shot peening, the shot and the matrix collide with each other, causing elastic and plastic deformation on the alloy surface, and changing the alloy surface from an uneven tensile stress state to a uniform compressive stress state, thereby improving the mechanical properties, refining the aluminum-silver alloy particles, increasing the grain boundaries, and providing space for the silver element to diffuse to the surface. The channels lead to the enrichment of silver elements on the alloy surface, which enhances the conductivity. Through shot peening, a large number of undulating pits are formed on the alloy surface, which increases the surface energy of the alloy. Under the high-frequency impact generated by ultrasound, these pits form a gradient nanostructure, which increases the specific surface area of the alloy, thereby improving the conductivity and increasing the content of oxygen elements on the surface of the alloy. Further oxidation treatment increases the thickness and acceptor density of the formed oxide film. Shot peening not only refines the grains but also breaks up the heterogeneous phase particles, thereby improving the integrity and uniformity of the oxide film, and forming a dense stacking effect between the oxide film layer and the surface microcrystalline structure. When a small amount of chloride ions penetrate into it, the surface structure produces a "maze" effect, which prolongs the transmission path of corrosive ions to the inside of the metal matrix, while reducing the aggregation of corrosive ions, inhibiting the transformation from metastable pitting to stable pitting, and improving the corrosion resistance of the alloy.
[0020] Secondly, wrap and coat graphite fibers around the alloy surface, thereby increasing the diameter of the cable material, reducing the matrix resistance, allowing more and stronger current to flow through, and at the same time, improving the problem of uneven current distribution. Then, weave carbon fibers into a net so that the alloy and graphite fibers are coated therein, thereby playing a role in protecting the conductive material, enhancing the mechanical properties and corrosion resistance of the cable. And when the duration of the power frequency impact current is relatively long, the graphite further expands due to the generated heat, only causing a change in the density of the graphite part in the inner core of the cable material, so that the resistance change rate of the composite conductive material during long-term operation is smaller, enhancing the conductivity of the matrix. Detailed implementation mode
[0021] Next, in combination with the embodiments of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.
[0022] In order to more clearly illustrate the method provided by the present invention, the following embodiments are used for detailed description. The test methods for each index of the corrosion-resistant cross-linked cable manufactured in the following embodiments are as follows:
[0023] Conductivity: Take the same-sized examples and comparative examples and refer to GB / T21698 to detect their resistivity.
[0024] Corrosion resistance: Take the same-sized examples and comparative examples, bury them in alkaline soil for an accelerated corrosion test. The soil temperature is 60°C, the water content is 20%, the total salt content is 18%, the pH is 9.5, and the time is 1000h. Then test their resistivity.
[0025] Mechanical properties: Take the same-sized examples and comparative examples and refer to GB / T228.1 to test their tensile strength.
[0026] Example 1
[0027] (1) Mix cerium powder, lanthanum powder, and yttrium powder in a mass ratio of 1:1:1 to obtain a rare earth material; heat the magnesium alloy and aluminum ingot to 750°C to fully melt the two, add the rare earth material, heat to 1200°C, stir at 40 rpm for 40 min, and then cool to obtain intermediate A; the mass ratio of the magnesium alloy, aluminum ingot, and rare earth material is 5:5:0.5; the mass percentage of the chemical composition of the magnesium alloy is: magnesium 94.94%, aluminum 3.5%, silicon 1.5%, zinc 0.04%, iron 0.01%, copper 0.01%;
[0028] (2) Heat the magnesium alloy and aluminum ingot to 750 °C to fully melt them. Add intermediate A and oxygen-free silver, then heat to 900 °C and hold for 12 min. Press hexachloroethane into the bottom of the molten metal for stirring degassing and slagging. The dosage of hexachloroethane is 0.3% of the furnace charge. Then remove the surface dross, cast into a mold, cool and solidify. Then, carry out homogenization annealing at a temperature of 360 °C for 10 h. Next, perform ultrasonic shot peening. The process parameters are as follows: the shot peening particles are 100CR6 rolling bearing steel balls with a diameter of 2 mm, the number of particles is 300, the air pressure is 0.1 MPa, the moving speed of the nozzle is 1.5 m / min, the ultrasonic power is 1500 W, the frequency is 21 kHz, and the time is 40 s. Finally, perform oxidation treatment at 500 °C for 40 min to obtain the alloy material; the mass ratio of the magnesium alloy, aluminum ingot, intermediate A, and oxygen-free silver is 5:5:0.5:0.5;
[0029] (3) Cut the expanded graphite paper with a thickness of 0.5 mm into filaments with a length of 25 cm and a width of 0.5 mm, wrap it around the alloy material to obtain a composite conductive material. Then, weave and wrap carbon fiber around the composite material to make a carbon fiber mesh with a grammage of 150 g / m 2 and a strength of 3000 MPa, with a thickness of 0.5 mm. Finally, cover it with low-density polyethylene with a molecular weight of 153500 as a protective layer with a thickness of 2.5 mm to obtain a corrosion-resistant cross-linked cable.
[0030] Example 2
[0031] (1) Mix cerium powder, lanthanum powder, and yttrium powder according to a mass ratio of 1:1:1 to obtain a rare earth material; heat the magnesium alloy and aluminum ingot to 800 °C to fully melt them. Add the rare earth material, then heat to 1300 °C and stir at 60 rpm for 55 min. Then cool to obtain intermediate A; the mass ratio of the magnesium alloy, aluminum ingot, and rare earth material is 5:5:1.2; the mass percentage of the chemical composition of the magnesium alloy is: magnesium 94.94%, aluminum 3.5%, silicon 1.5%, zinc 0.04%, iron 0.01%, copper 0.01%;
[0032] (2) Heat the magnesium alloy and aluminum ingot to 830 °C to fully melt them. Add intermediate A and oxygen-free silver, then heat to 1000 °C and hold for 16 min. Inject hexachloroethane into the bottom of the molten metal for stirring degassing and slag formation. The dosage of hexachloroethane is 0.35% of the furnace charge. Then remove the surface dross, cast into a mold, cool and solidify. Subsequently, perform homogenization annealing at a temperature of 390 °C for 12 h. Then, perform ultrasonic shot peening. The process parameters are as follows: the shot peening pellets are 100CR6 rolling bearing steel balls with a diameter of 2 mm, the number of pellets is 300, the air pressure is 0.1 MPa, the moving speed of the nozzle is 1.5 m / min, the ultrasonic power is 1500 W, the frequency is 21 kHz, and the time is 70 s. Finally, perform oxidation treatment at 550 °C for 60 min to obtain the alloy material; the mass ratio of the magnesium alloy, aluminum ingot, intermediate A, and oxygen-free silver is 5:5:0.75:1.4;
[0033] (3) Cut the expanded graphite paper with a thickness of 0.5 mm into filaments with a length of 40 cm and a width of 0.8 mm, wrap it around the alloy material to obtain a composite conductive material. Then, weave and wrap carbon fiber around the composite material to make a carbon fiber mesh with a grammage of 200 g / m 2 and a strength of 3800 MPa, with a thickness of 1.2 mm. Finally, cover it with low-density polyethylene with a molecular weight of 153500 as a protective layer with a thickness of 2.5 mm to obtain a corrosion-resistant cross-linked cable.
[0034] Example 3
[0035] (1) Mix cerium powder, lanthanum powder, and yttrium powder according to a mass ratio of 1:1:1 to obtain a rare earth material; heat the magnesium alloy and aluminum ingot to 900 °C to fully melt them. Add the rare earth material, then heat to 1500 °C and stir at 80 rpm for 70 min. Then cool to obtain intermediate A; the mass ratio of the magnesium alloy, aluminum ingot, and rare earth material is 5:5:2; the mass percentage of the chemical composition of the magnesium alloy is: magnesium 94.94%, aluminum 3.5%, silicon 1.5%, zinc 0.04%, iron 0.01%, copper 0.01%;
[0036] (2) Heat the magnesium alloy and aluminum ingots to 900 °C to fully melt them. Add intermediate A and oxygen-free silver, then heat to 1100 °C and hold for 20 min. Press hexachloroethane into the bottom of the molten metal for stirring to degas and slag. The dosage of hexachloroethane is 0.4% of the furnace charge. Then remove the surface dross, pour into the mold, and cool and solidify. Then, perform homogenization annealing at a temperature of 450 °C for 15 h. Next, perform ultrasonic shot peening. The process parameters are as follows: the shot peening particles are 100CR6 rolling bearing steel balls with a diameter of 2 mm, the number of particles is 300, the air pressure is 0.1 MPa, the moving speed of the nozzle is 1.5 m / min, the ultrasonic power is 1500 W, the frequency is 21 kHz, and the time is 100 s. Finally, perform oxidation treatment at 600 °C for 80 min to obtain the alloy material; the mass ratio of the magnesium alloy, aluminum ingot, intermediate A, and oxygen-free silver is 5:5:1:2;
[0037] (3) Cut the expanded graphite paper with a thickness of 0.5 mm into filaments with a length of 50 cm and a width of 1 mm, wrap it around the alloy material to obtain a composite conductive material. Then, weave and wrap carbon fiber around the composite material to make a carbon fiber net with a grammage of 250 g / m 2 and a strength of 4500 MPa, with a thickness of 2 mm. Finally, cover it with low-density polyethylene with a molecular weight of 153500 as a protective layer with a thickness of 2.5 mm to obtain a corrosion-resistant cross-linked cable.
[0038] Comparative Example 1
[0039] The difference between Comparative Example 1 and Example 2 lies in that steps (1) and (2) are different. Modify step (1) as follows: Mix cerium powder, lanthanum powder, and yttrium powder according to a mass ratio of 1:1:1 to obtain a rare earth material; heat the aluminum ingot to 800 °C to fully melt it, add the rare earth material, heat to 1300 °C, stir at 60 rpm for 55 min, and then cool to obtain intermediate A; the mass ratio of the aluminum ingot to the rare earth material is 10:1.2;
[0040] Modify step (2) as follows: Heat the aluminum ingot to 830 °C to fully melt it, add intermediate A and oxygen-free silver, heat to 1000 °C, hold for 16 min, inject hexachloroethane into the bottom of the molten metal for stirring degassing and slag formation. The dosage of hexachloroethane is 0.35% of the furnace charge. Subsequently, remove the surface dross, cast into a mold, cool and solidify. Then, perform homogenization annealing at a temperature of 390 °C for 12 h. Next, perform ultrasonic shot peening. The process parameters are as follows: the shot peening particles are 100CR6 rolling bearing steel balls with a diameter of 2 mm, the number of particles is 300, the air pressure is 0.1 MPa, the moving speed of the nozzle is 1.5 m / min, the ultrasonic power is 1500 W, the frequency is 21 kHz, and the time is 70 s. Finally, perform oxidation treatment at 550 °C for 60 min to obtain the alloy material. The mass ratio of the aluminum ingot, intermediate A, and oxygen-free silver is 10:0.75:1.4. The remaining steps are the same as in Example 2.
[0041] Comparative Example 2
[0042] The difference between Comparative Example 2 and Example 2 lies in that steps (1) and (2) are different. Modify step (1) as follows: Mix cerium powder, lanthanum powder, and yttrium powder according to a mass ratio of 1:1:1 to obtain a rare earth material. Heat the magnesium alloy to 800 °C to fully melt it, add the rare earth material, heat to 1300 °C, stir at 60 rpm for 55 min, and then cool to obtain intermediate A. The mass ratio of the magnesium alloy to the rare earth material is 10:1.2. The mass percentages of the chemical components of the magnesium alloy are as follows: magnesium 94.94%, aluminum 3.5%, silicon 1.5%, zinc 0.04%, iron 0.01%, and copper 0.01%.
[0043] Modify step (2) as follows: Heat the magnesium alloy to 830 °C to fully melt it, add intermediate A and oxygen-free silver, heat to 1000 °C, hold for 16 min, inject hexachloroethane into the bottom of the molten metal for stirring degassing and slag formation. The dosage of hexachloroethane is 0.35% of the furnace charge. Subsequently, remove the surface dross, cast into a mold, cool and solidify. Then, perform homogenization annealing at a temperature of 390 °C for 12 h. Next, perform ultrasonic shot peening. The process parameters are as follows: the shot peening particles are 100CR6 rolling bearing steel balls with a diameter of 2 mm, the number of particles is 300, the air pressure is 0.1 MPa, the moving speed of the nozzle is 1.5 m / min, the ultrasonic power is 1500 W, the frequency is 21 kHz, and the time is 70 s. Finally, perform oxidation treatment at 550 °C for 60 min to obtain the alloy material. The mass ratio of the magnesium alloy, intermediate A, and oxygen-free silver is 10:0.75:1.4. The remaining steps are the same as in Example 2.
[0044] Comparative Example 3
[0045] The difference between Comparative Example 3 and Example 2 lies in step (2). Step (2) is changed to: Heat the magnesium alloy and aluminum ingot to 830°C to fully melt them. Add intermediate A, heat to 1000°C, hold for 16 min, inject hexachloroethane into the bottom of the molten metal for stirring degassing and slagging. The dosage of hexachloroethane is 0.35% of the furnace charge. Then remove the surface dross, cast into a mold, cool and shape. Then, perform homogenization annealing at a temperature of 390°C for 12 h. Next, perform ultrasonic shot peening. The process parameters are: the shot peening pellets are 100CR6 rolling bearing steel balls with a diameter of 2 mm, the number of pellets is 300, the air pressure is 0.1 MPa, the nozzle moving speed is 1.5 m / min, the ultrasonic power is 1500 W, the frequency is 21 kHz, and the time is 70 s. Finally, perform oxidation treatment at 550°C for 60 min to obtain the alloy material; the mass ratio of the magnesium alloy, aluminum ingot, and intermediate A is 5:5:0.75; the remaining steps are the same as those in Example 2.
[0046] Comparative Example 4
[0047] The difference between Comparative Example 4 and Example 2 is that step (1) is absent. Step (2) is changed to: Heat the magnesium alloy and aluminum ingot to 830°C to fully melt them. Add oxygen-free silver, heat to 1000°C, hold for 16 min, inject hexachloroethane into the bottom of the molten metal for stirring degassing and slagging. The dosage of hexachloroethane is 0.35% of the furnace charge. Then remove the surface dross, cast into a mold, cool and shape. Then, perform homogenization annealing at a temperature of 390°C for 12 h. Next, perform ultrasonic shot peening. The process parameters are: the shot peening pellets are 100CR6 rolling bearing steel balls with a diameter of 2 mm, the number of pellets is 300, the air pressure is 0.1 MPa, the nozzle moving speed is 1.5 m / min, the ultrasonic power is 1500 W, the frequency is 21 kHz, and the time is 70 s. Finally, perform oxidation treatment at 550°C for 60 min to obtain the alloy material; the mass ratio of the magnesium alloy, aluminum ingot, and oxygen-free silver is 5:5:1.4; the remaining steps are the same as those in Example 2.
[0048] Comparative Example 5
[0049] The difference between Comparative Example 5 and Example 2 lies in step (2). Step (2) is modified as follows: Heat the magnesium alloy and aluminum ingot to 830°C, fully melt the two, add intermediate A and oxygen-free silver, heat to 1000°C, hold for 16 min, press hexachloroethane into the bottom of the molten metal for stirring degassing and slag formation. The dosage of hexachloroethane is 0.35% of the furnace charge. Then remove the surface dross, cast into a mold, cool and shape. Thereafter, perform homogenization annealing at a temperature of 390°C for 12 h. Then, perform shot peening. The process parameters are as follows: the shot peening shot is 100CR6 rolling bearing steel balls with a diameter of 2 mm, the number of shot is 300, the air pressure is 0.1 MPa, the moving speed of the nozzle is 1.5 m / min, the time is 70 s. Finally, perform oxidation treatment at 550°C for 60 min to obtain the alloy material. The mass ratio of the magnesium alloy, aluminum ingot, intermediate A, and oxygen-free silver is 5:5:0.75:1.4. The remaining steps are the same as those in Example 2.
[0050] Comparative Example 6
[0051] The difference between Comparative Example 6 and Example 2 lies in step (2). Step (2) is modified as follows: Heat the magnesium alloy and aluminum ingot to 830°C, fully melt the two, add intermediate A and oxygen-free silver, heat to 1000°C, hold for 16 min, press hexachloroethane into the bottom of the molten metal for stirring degassing and slag formation. The dosage of hexachloroethane is 0.35% of the furnace charge. Then remove the surface dross, cast into a mold, cool and shape. Thereafter, perform homogenization annealing at a temperature of 390°C for 12 h. Then, perform oxidation treatment at 550°C for 60 min to obtain the alloy material. The mass ratio of the magnesium alloy, aluminum ingot, intermediate A, and oxygen-free silver is 5:5:0.75:1.4. The remaining steps are the same as those in Example 2.
[0052] Comparative Example 7
[0053] The difference between Comparative Example 7 and Example 2 lies in step (2). Step (2) is modified as follows: Heat the magnesium alloy and aluminum ingot to 830°C, fully melt the two, add intermediate A and oxygen-free silver, heat to 1000°C, hold for 16 min, press hexachloroethane into the bottom of the molten metal for stirring degassing and slag formation. The dosage of hexachloroethane is 0.35% of the furnace charge. Then remove the surface dross, cast into a mold, cool and shape. Thereafter, perform homogenization annealing at a temperature of 390°C for 12 h. Then, perform ultrasonic shot peening. The process parameters are as follows: the shot peening shot is 100CR6 rolling bearing steel balls with a diameter of 2 mm, the number of shot is 300, the air pressure is 0.1 MPa, the moving speed of the nozzle is 1.5 m / min, the ultrasonic power is 1500 W, the frequency is 21 kHz, and the time is 70 s to obtain the alloy material. The mass ratio of the magnesium alloy, aluminum ingot, intermediate A, and oxygen-free silver is 5:5:0.75:1.4. The remaining steps are the same as those in Example 2.
[0054] Comparative Example 8
[0055] The difference between Comparative Example 8 and Example 2 lies in step (3). Step (3) is modified as follows: The carbon fiber is woven and coated on the alloy material to form a carbon fiber mesh with a grammage of 200 g / m 2 , a strength of 3800 MPa, a thickness of 1.2 mm, and finally a low-density polyethylene with a molecular weight of 153500 is coated as a protective layer with a thickness of 2.5 mm to obtain a corrosion-resistant cross-linked cable; the remaining steps are the same as those in Example 2.
[0056] Comparative Example 9
[0057] The difference between Comparative Example 9 and Example 2 lies in step (3). Step (3) is modified as follows: The expanded graphite paper with a thickness of 0.5 mm is cut into filaments with a length of 40 em and a width of 0.8 mm, coated on the alloy material, and finally a low-density polyethylene with a molecular weight of 153500 is coated as a protective layer with a thickness of 2.5 mm to obtain a corrosion-resistant cross-linked cable; the remaining steps are the same as those in Example 2.
[0058] Effect Example
[0059] The following Table 1 shows the performance analysis results of the corrosion-resistant cross-linked cables of Examples 1 to 3 and Comparative Examples 1 to 9 of the present invention.
[0060] Table 1
[0061]
[0062]
[0063] From the comparison of the experimental results between the examples and the comparative examples in Table 1, it can be found that in the present invention, magnesium and aluminum are used as the matrix, and silver is dispersed as the second phase in the alloy matrix to form a solid solution, and an aluminum-silver alloy or an aluminum-magnesium-silicon alloy strengthening phase is generated, thereby improving the corrosion resistance of the matrix and achieving electrical conductivity. At the same time, rare earth elements are added, which is beneficial to the exertion of the solid solution strengthening effect of alloy elements, achieving the effects of refining grains, improving the electronegativity of each micro-region on the surface of the composite material and stabilizing the protective film layer, and improving the corrosion protection performance of the alloy. Then, ultrasonic shot peening treatment is carried out. Under the action of high-energy shot peening, elastic and plastic deformation occurs on the alloy surface, and the surface of the alloy changes from an uneven tensile stress state to a uniform compressive stress state, improving the mechanical properties, and refining the aluminum-silver alloy particles, increasing the grain boundaries, providing a diffusion channel for silver elements to diffuse to the surface layer, enhancing the electrical conductivity, and forming pits with a gradient nanostructure on the surface under the action of the high-frequency impact generated by ultrasonic waves, increasing the specific surface area of the alloy, thereby improving the conduction performance, and at the same time increasing the content of oxygen elements on the alloy surface layer. Further through oxidation treatment, the thickness and acceptor density of the formed oxide film are increased. Moreover, shot peening not only refines grains but also fragments heterogeneous phase particles, thereby improving the integrity and uniformity of the oxide film. When a small amount of chloride ions penetrate into it, a "labyrinth" effect is generated on the surface layer structure, prolonging the transmission path of corrosive ions to the interior of the metal matrix and improving the corrosion resistance of the alloy. Then, using the alloy as a framework, graphite fibers are wound and coated on its surface, thereby increasing the diameter of the material and enhancing the electrical conductivity. Then, carbon fibers are woven into a net so that the alloy and graphite fibers are wrapped therein, thereby playing a role in protecting the composite material, enhancing the mechanical properties and corrosion resistance of the cable, and enhancing the long-term electrical conductivity of the matrix.
[0064] For those skilled in the art, it is obvious that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic characteristics of the present invention. Therefore, from any point of view, the embodiments should be regarded as exemplary and non-limiting. The scope of the present invention is defined by the appended claims rather than the above description. Therefore, all changes falling within the meaning and scope of the equivalent elements of the claims are intended to be included in the present invention. Any reference signs in the claims should not be construed as limiting the claimed claim.
Claims
1. A corrosion-resistant cross-linked cable, characterized in that: The corrosion-resistant cross-linked cable is made of an alloy of magnesium, aluminum, silver and rare earth, and graphite fiber is compositely coated on the surface, and then a mesh woven from carbon fiber is coated on the surface of the composite material; the preparation method of the corrosion-resistant cross-linked cable comprises the following preparation steps: (1) The magnesium alloy and the aluminum ingot are heated to 750-900°C to fully melt the two, rare earth materials are added, the temperature is raised to 1200-1500°C, stirred at 40-80 rpm for 40-70 min, and then cooled to obtain intermediate A; (2) heating the magnesium alloy and the aluminum ingot to 750-900°C to fully melt the two, adding the intermediate A and the oxygen-free silver, heating to 900-1100°C, keeping the temperature for 12-20 minutes, pressing hexachloroethane into the bottom of the molten metal to stir and degas and slag, then removing the surface scum, casting the mold, cooling and finalizing, and then performing homogenization annealing treatment at a temperature of 360-450°C for 10-15 hours, and then performing ultrasonic shot peening and oxidation treatment in sequence to obtain an alloy material; (3) Cutting expanded graphite paper with a thickness of 0.5 mm into filaments and coating the filaments on the alloy material to obtain a composite conductive material, then coating the composite material with carbon fiber weaving to make a carbon fiber mesh with a thickness of 0.5 to 2 mm, and finally coating it with a low-density polyethylene with a molecular weight of 153,500 as a protective layer with a thickness of 2.5 mm to obtain a corrosion-resistant cross-linked cable.
2. A corrosion-resistant cross-linked cable according to claim 1, characterized in that: The mass percentages of the chemical components of the magnesium alloy in step (1) are: 94.94% magnesium, 3.5% aluminum, 1.5% silicon, 0.04% zinc, 0.01% iron, and 0.01% copper.
3. A corrosion-resistant cross-linked cable according to claim 1, characterized in that: The rare earth material in step (1) is composed of cerium powder, lanthanum powder and yttrium powder in a mass ratio of 1:1:
1.
4. A corrosion-resistant cross-linked cable according to claim 1, characterized in that: In step (1), the mass ratio of the magnesium alloy, the aluminum ingot and the rare earth material is 5:5:0.5-2.
5. The corrosion-resistant cross-linked cable according to claim 1, characterized in that: The amount of hexachloroethane used in step (2) is 0.3-0.4% of the furnace amount.
6. A corrosion-resistant cross-linked cable according to claim 1, characterized in that: The process parameters of the ultrasonic shot peening in step (2) are as follows: the shot peening pellets are 100CR6 rolling bearing steel balls with a diameter of 2 mm, the number of pellets is 300, the air pressure is 0.1 MPa, the nozzle movement speed is 1.5 m / min, the ultrasonic power is 1500 W, the frequency is 21 kHz, and the time is 40 to 100 s.
7. The corrosion-resistant cross-linked cable according to claim 1, characterized in that: The oxidation conditions in step (2) are: temperature of 500-600° C. and time of 40-80 min.
8. The corrosion-resistant cross-linked cable according to claim 1, characterized in that: In step (2), the mass ratio of the magnesium alloy, the aluminum ingot, the intermediate A, and the oxygen-free silver is 5:5:0.5-1:0.5-2.
9. The corrosion-resistant cross-linked cable according to claim 1, characterized in that: The length of the filament in step (3) is 25 to 50 cm and the width is 0.5 to 1 mm.
10. The corrosion-resistant cross-linked cable according to claim 1, characterized in that: The carbon fiber mesh in step (3) has a gram weight of 150 to 250 g / m 2 , strength is 3000~4500MPa.